Upgrading Teachers’ Professionalism through Class Observation-based-Publication Training - Dian Rianita; Alexsander Yandra; Khuriyatul Husna; Adia Ferizko (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
It is well-known that a teacher's primary responsibility is as an educator and facilitator for his pupils. However, in order to become more professional, teachers also need to improve their academic qualifications and skills to keep up with changes in science and technology. In particular, they need to publish scientific articles that share the knowledge they use in the classroom. Therefore, the purpose of this community service project is to help the teachers at SMA Negeri 1 Tualang with their publication endeavors, including the crafting of articles based on the best practice of their class observations and the implementation of the open journal system (OJS) for their submission. The activity is conducted conceptually and practically to make a significant contribution by making it easier for participating teachers to carry out the process of creating best practice articles and submitting them autonomously.